2011
DOI: 10.3109/07434618.2011.587830
|View full text |Cite
|
Sign up to set email alerts
|

Communication and AAC in the Lives of Adults with Autism: The Stories of Their Older Parents

Abstract: The aim of this study was to explore the communication experiences, particularly those related to augmentative and alternative communication (AAC), of older parents who had an adult son or daughter with autism. A narrative analysis of in-depth interviews with 16 older parents indicated that the majority had rarely spontaneously mentioned AAC or other communication interventions. Most did not express the need for such services. Yet, communication breakdown featured prominently in parents' narratives about inter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
15
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 26 publications
(18 reference statements)
0
15
0
Order By: Relevance
“…The methodology has been described in‐depth elsewhere (Hines et al . ). Key aspects of the methodology are provided below.…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…The methodology has been described in‐depth elsewhere (Hines et al . ). Key aspects of the methodology are provided below.…”
Section: Methodsmentioning
confidence: 97%
“…The study was conducted in full accordance with ethical principles, including the guidelines of the Helsinki Declaration. The methodology has been described in-depth elsewhere (Hines et al 2011). Key aspects of the methodology are provided below.…”
Section: Methodsmentioning
confidence: 99%
“…Another qualitative study with 16 Australian older parents with a child diagnosed with ASD investigated the augmentative and alternative communication experiences and their impacts on caregivers’ gratification and/or stress. Results indicated that the quality of communication has tremendous effects on both caregivers’ stress and gratification (Hines, Balandin, & Togher, ).…”
mentioning
confidence: 99%
“…(Donato et al, 2014, p. 118). In addition, some parents did not accept the need for AAC, reportedly due to their belief that their child could already communicate, or conversely did not want to communicate (Binger, Kent-Walsh, Berens, Del Campo, & Rivera, 2008;Hines et al, 2011;Lindsay, 2010;Stephenson & Dowrick, 2005). Furthermore, teachers interviewed by Pickl (2011) discussed parents who were resistant to AAC due to their perception of the cause of their child's disability, and therefore sought alternative 'cures'.…”
Section: Body Functionsmentioning
confidence: 99%
“…However, other parents reported that they facilitated the use of AAC by managing their time, streamlining their efforts, planning in advance, and making AAC a part of their everyday routine (Calculator, 2002). Furthermore, both parents and professionals agreed that family advocacy and ownership of the intervention was important for the use of AAC systems across settings (Goldbart & Marshall, 2004;Hines et al, 2011;Lund & Light, 2007;Trembath et al, 2014), with one parent noting that "there are not many kids I think like…”
Section: Body Functionsmentioning
confidence: 99%